Persepsi Peserta Program Bantuan Langsung Tunai Terhadap Kepercayaan Publik di Desa Cintai Damai Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Novri Sari MP Pasaribu; Dara Aisyah (Universitas Warmadewa, 2024)
The Direct Cash Assistance (BLT) program in Indonesia aims to alleviate economic hardship, particularly during the COVID-19 pandemic. It seeks to boost purchasing power and mitigate the crisis's impact. While BLT is seen as a potential solution to poverty and economic instability, its success hinges on public trust. This study analyzes community perceptions and trust in the BLT program in Cinta Damai Village. Using a mixed-methods approach, the research found a positive perception among recipients who acknowledged the benefits of BLT funds. However, concerns persist regarding fairness and transparency in the program's implementation. The study concludes that a positive public perception enhances trust, with 21% of trust variability explained by perception, while other factors remain unexplored.